Does sensorimotor training improve the static balance of young volleyball players? - Pau, M.; Loi, A.; Pezzotta, M. C. (Sports Biomechanics, 2012)
The aim of this investigation is to assess the effectiveness of a 6-week balance training (BT) protocol, integrated in regular training sessions, on postural sway of young female volleyball players (n = 26, age 13.0 ± 0.2 years) divided into two groups (intervention and control; 13 per group). Trials were performed for bipedal and unipedal stance conditions before and after the BT protocol, using a pressure platform to collect center-of-pressure (COP) time series that were processed to calculate sway area, COP path length, and maximum displacement range in anteroposterior and mediolateral directions. The intervention group exhibited smaller sway areas in eyes closed conditions (intervention = 42.76 mm2, control = 67.60 mm2; p < 0.05) and Romberg quotients (intervention = 1.11 mm, control = 1.82 mm) in bipedal stance, while all the other parameters were unaffected. BT also reduced sway area (intervention = 122.70 mm2, control = 187.18 mm2) and anteroposterior COP displacements (intervention = 20.18 mm, control = 22.38 mm) of the non-dominant limb for single-leg stance. No significant change was found for the dominant limb. Although it is possible to hypothesize a beneficial effect of BT on young athletes, further investigations are required to clarify its actual effect on balance performance with respect to normal volleyball training.